A Perspective-Based Simulation Game to Explore Future Pathways of a Water-Society System Under Climate Change. (April 2013) - Valkering, Pieter; van der Brugge, Rutger; Offermans, Astrid; Haasnoot, Marjolijn; Vreugdenhil, Heleen
In this article, the authors address the challenge of including societal responses, society-environment interactions, discontinuity, and surprise in environmental scenario analysis. They do so through developing and testing a perspective-based simulation game for a typical Dutch river stretch. Concepts deriving from Cultural Theory, the Advocacy Coalition Framework, and Transition Theory provide the input for the game design. Players take on the role of water managers, responding to events and developments in the water-society system under specific realizations of a climate scenario. Responses include the choice for specific river management options, changing coalition perspectives, and changes in advocacy coalition membership. A pilot case study shows that the simulation game is a useful tool to explore possible future river management dynamics. It generates relevant insights in the water management strategies that may be chosen under future conditions, the possible drivers underlying future societal perspective change, and the way advocacy coalitions may interact. As such, the simulation game offers great potential for developing and assessing policy relevant climate adaptation pathways, in which water-society interaction, discontinuity, and surprise is taken explicitly into account. The main challenges for future research include reducing game complexity, better representing changes in the advocacy coalitions' strengths, and exploring more fundamental societal perspective shifts.